Lipid-Rich Extract from Mexican Avocado Seed (Persea americana var. drymifolia) Reduces Staphylococcus aureus Internalization and Regulates Innate Immune Response in Bovine Mammary Epithelial Cells. (12th September 2019) - Báez-Magaña, Marisol; Ochoa-Zarzosa, Alejandra; Alva-Murillo, Nayeli; Salgado-Garciglia, Rafael; López-Meza, Joel Edmundo
Abstract : Bovine mammary epithelial cells (bMECs) are capable of initiating an innate immune response (IIR) to invading bacteria. Staphylococcus aureus is not classically an intracellular pathogen, although it has been shown to be internalized into bMECs. S. aureus internalizes into nonprofessional phagocytes, which allows the evasion of the IIR and turns antimicrobial therapy unsuccessful. An alternative treatment to control this pathogen is the modulation of the innate immune response of the host. The Mexican avocado ( Persea americana var. drymifolia) is a source of molecules with anti-inflammatory and immunomodulatory properties. Hence, we analyze the effect of a lipid-rich extract from avocado seed (LEAS) on S. aureus internalization into bMECs and their innate immunity response. The effects of LEAS (1-500 ng/ml) on the S. aureus growth and bMEC viability were assessed by turbidimetry and MTT assays, respectively. LEAS did not show neither antimicrobial nor cytotoxic effects. S. aureus internalization into bMECs was analyzed by gentamicin protection assays. Interestingly, LEAS (1-200 ng/ml) decreased bacterial internalization (60-80%) into bMECs. This effect correlated with NO production and the induction of the gene expression of IL-10, while the expression of the proinflammatory cytokine TNF- α was reduced. These effects could be related to the inhibition of MAPK p38 (∼60%) activation by LEAS. In conclusion, our results showed that LEAS inhibits the S. aureus internalization into bMECs and modulates the IIR, which indicates that avocado is a source of metabolites for control of mastitis pathogens.